The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fmicb.2022.912297
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gene Repression on Biofilm Formation of Vibrio cholerae

Abstract: Vibrio cholerae, the etiological agent of cholera, is a facultative intestinal pathogen which can also survive in aquatic ecosystems in the form of biofilms, surface-associated microbial aggregates embedded in an extracellular matrix, which protects them from predators and hostile environmental factors. Biofilm-derived bacteria and biofilm aggregates are considered a likely source for cholera infections, underscoring the importance of V. cholerae biofilm research not just to better understand bacterial ecology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Therefore, an exciting question for the future will be whether d -Arg’s dual function as a broad-spectrum toxin and chemotactic warning signal could play a role in biofilm destablization and dispersal. In this line, a study recently reported that the MCP DRK -BsrV operon ( vc1313-1312 ) is part of the in-biofilm repressome and that constitutive expression of some of these genes interferes with biofilm formation 53 . However, the loss of MCP DRK was reported to have no effect on V. cholerae’s fitness in infection or dissemination 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an exciting question for the future will be whether d -Arg’s dual function as a broad-spectrum toxin and chemotactic warning signal could play a role in biofilm destablization and dispersal. In this line, a study recently reported that the MCP DRK -BsrV operon ( vc1313-1312 ) is part of the in-biofilm repressome and that constitutive expression of some of these genes interferes with biofilm formation 53 . However, the loss of MCP DRK was reported to have no effect on V. cholerae’s fitness in infection or dissemination 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Predicting the GFP expression profile (GEEP) of a bacteria biofilm over a Petri dish based on the chemical stimulus release profile (i.e., spatial, time, and concentration) has several potential applications. GEEP prediction can help researchers understand how biofilms respond to different chemical stimulus release profiles, aiding in the development of strategies to control or enhance biofilm formation in various natural and engineered environments [2]. Also, profile prediction can help to identify novel targets for antimicrobial therapies and develop strategies to disrupt or prevent biofilm formation [3], [4].…”
Section: Introductionmentioning
confidence: 99%